Implementation of the GeoGebra software tool for geometrical reasoning competition in ninth grade students (2019)
The study developed, and which is presented succinctly in this report, aimed to implement an intervention plan with the GeoGebra software tool for geometric reasoning in ninth grade students of the San José Educational Institution of the city of San José de Cúcuta. Methodologically, it is a quasi-experimental study of pretest and posttest with control group. The pretest showed flaws in Geometric Reasoning in the students, both in the control and experimental groups. These results led to the design and implementation of a Treatment Plan for the experimental group using the GeoGebra software tool. After applying the posttest, it was demonstrated, through its results, that the Plan was highly significant, since a high percentage of the students of the experimental group correctly answered the questions of the instrument on geometric reasoning.